Measuring the effectiveness of career education at a medical university and future issues from the perspective of students’ transformation: impact of a new career education program at a medical university on entrepreneurship effectiveness - Shuichi Murakawa; Junko Ishiguro; Akiko Watanabe (Fujita Medical Journal)
Objectives: The current study aimed to examine the effectiveness of a new career education course, “Career Development Theory,” at a medical university. This course is designed to enable students to plan their careers and consider various career options. This class was introduced to improve students’ entrepreneurial qualities and broaden their career choices. Methods: The research methods included a survey to measure entrepreneurial qualities before and after attending the class and an analysis of students’ reports of what they had learned from the class. A total of 243 students who plan to qualify to participate in the national examinations for clinical technologists, clinical engineering technologists, and radiology technologists participated in the research. Results: The results revealed that autonomy and creativity scores significantly increased, whereas risk-taking scores decreased. This suggests that the class may have taught students accurate self- and risk-assessment skills while fostering a cautious attitude toward avoiding unnecessary risks. The report analysis indicated that students’ self-awareness and attitudes toward their careers changed because of the class. Many students felt that their career options had expanded and found avenues outside the medical profession. Conclusions: This research demonstrates the need for and effectiveness of career education in medical universities and provides valuable suggestions for improving educational programs. The future goal is for more students to design their careers freely and choose the path that best suits them from various career options. The current results may provide a useful reference for career education curriculum development at other medical universities.